A Berry-Esseen Bound for Nonlinear Statistics with Bounded Differences (Statistics, Optimization & Information Computing, 2021)
In this paper, we obtain an explicit Berry-Esseen bound in the central limit theorem for nonlinear statistics with bounded differences. Some examples are provided as well.